Analisis Konflik antara UMKM dengan TIKTOK Shop - Mauliza, Chusna Amanda (Crises on Languages and Literature, 2024)
The topic of TikTok Shop's impact on local MSMEs is a relevant issue because it highlights unfair business competition, especially with the presence of e-commerce platforms integrated with social media such as TikTok. The conflict includes debates between regulators, entrepreneurs, and academics about regulations, economic impacts, and the protection of local MSMEs in facing competition with large sellers affiliated with the platform.